Pendampingan Pembuatan Media Promosi Pariwisata International Berbasis Digital Bagi Warga Desa Cisaat - Ihwan Rahman Bahtiar; Dwi Linda Kusuma; Yunilis Andika (Journal Of Human And Education (JAHE), 2023)
Village tourism is a tourism model that is currently developing in Indonesia. However, village tourism is constrained by the low awareness of residents to be involved in promoting it. Cisaat Village in Subang Regency, West Java, is one such village. The lack of skills to create digital-based promotional media is the cause of low public awareness of being actively involved in promoting Cisaat Village. This community service activity aims to train Cisaat villagers on making digital-based international promotional media. This activity was carried out considering that Cisaat Village has now begun to be visited by foreign tourists. This community service activity took place for two days offline. Based on the evaluation results of this service activity, it went well and smoothly. The indication is that activity participants gain new knowledge and skills in creating digital-based international promotional media and increase awareness of the ease of actively participating in promoting Cisaat Tourism Village even abroad.